Intrapulse Radar-Embedded Communications - Blunt, S D; Yatham, P; Stiles, J (IEEE transactions on aerospace and electronic systems, 2010)
The embedding of a covert communication signal amongst the ambient scattering from an incident radar pulse has previously been achieved by modulating a Doppler-like phase shift sequence over numerous pulses (i.e., on an inter-pulse basis). In contrast, this paper considers radar-embedded communications on an intrapulse basis whereby an incident radar waveform is converted into one of K communication waveforms, each of which acts as a communication symbol representing some predetermined information (e.g., a bit sequence). To preserve a low intercept probability, this manner of radar-embedded communications necessitates prudent selection of the set of communication waveforms as well as interference cancellation on receive. A general mathematical model and subsequent optimization problem is established for the design of the communication waveforms, from which three design strategies are developed. Also, receiver design issues are discussed, and an interference-canceling maximum likelihood receiver is presented. Performance results are presented in terms of the communication symbol error rate as well as a correlation-based metric from which intercept probability can be inferred. It is demonstrated that, given persistent radar illumination with a pulse repetition frequency (PRF) of 1-2 kHz, intrapulse radar-embedded communications can theoretically achieve data-rates commensurate with speech coding (for the interval of the radar dwell time) with the potential for even higher data-rates if additional diversity is appropriately incorporated.